Record of larvae and pupae of Aedes aegypti and Aedes albopictus in containers with saline water in natural conditions - de Brito Arduino, Marylene (2010)
To record the findings of dengue vector larvae and pupae in containers with saline water. Research was carried out during 14 months, where recipients were inspected, thus collecting larvae and pupae of Aedes aegypti and Aedes albopictus in a coastal city in the north of north state of São Paulo. Both physical and chemical parameters of the water were checked. Ae. aegypti and Ae. albopictus were found in all stages of developing as larvae, in saline water. The maximum concentration of salinity were 13,5% and 9,2% for the respective species. The salt was o o not found to be a limitation factor for evolution of both species. This has been the first registered case of these species, evolved in saline water, made in Brazil. These findings may cause severe, repercussions epidemiological, especially in the control of dengue.